An unusual case of eosinophilic uveitis in a cat. (22nd November 2021) - Newbold, Georgina M.; Premanandan, Chris
Abstract: An 8‐year‐old female spayed domestic short‐haired cat was examined for recurrent unilateral anterior uveitis of 5 month's duration. No underlying cause was found on infectious disease screening. The cat also had a 4‐year history of allergic or immune‐mediated skin disease that was controlled with corticosteroid injections followed by long‐term oral cyclosporine therapy. Medical management with frequent topical anti‐inflammatory drugs (prednisolone acetate 1% suspension, diclofenac 0.1% solution) controlled the intraocular inflammation; however, the uveitis would relapse when therapy was discontinued. Eventually, secondary glaucoma developed OD and the eye was enucleated. At the time of surgery, a complete blood count showed a mild eosinophilia. Histopathology revealed a marked panuveitis characterized by an abundant accumulation of mixed inflammatory cells, with a predominantly eosinophilic infiltrate in the anterior chamber, iris, ciliary body, and choroid. No etiologic agents were found on serial sections, and there were no cellular criteria for malignancy noted. Nine months after enucleation, the chronic dermatitis appeared to be in remission despite no further medical management. This is the first known report of a primarily eosinophilic uveitis in a cat with chronic allergic skin disease and may be considered an ocular variant of feline eosinophilic granuloma complex.